SOME TEXTUAL DIFFERENCES OF HAYDAR KHORAZMIY’S EPIC “MAKHZAN UL-ASROR” - Eshonqulova Feruza Husniddin qizi (PEDAGOGS, 2025)
Annotation: In this article, a number of textual deficiencies and differences are highlighted based on the examples of Haydar Khorazmi's epic "Makhzan ul-asrar" based on the copies of Cairo and London kept in Kazan, Tashkent, and the editions of Nodirbek Gaffarov's collections "Asrlar nidosi", "Mubarak Maktublar" and "Navoiyning nigohi tushgan".